Recent advances in the treatment of chronic liver diseases: focus on MASLD/MASH-related fibrosis - Jędrysik, Malwina; Chełstowska, Beata; Tomasiewicz, Krzysztof; Szymański, Filip M. (Clinical and Experimental Hepatology, 2026)
Chronic liver diseases (CLDs) represent a growing global health challenge, driven by the increasing prevalence of metabolic dysfunction-associated steatotic liver disease (MASLD), its progressive inflammatory-fibrotic form (metabolic dysfunction-associated steatohepatitis – MASH), as well as viral infections, alcoholic liver disease, and autoimmune and cholestatic disorders. Despite intensive research, effective pharmacological therapies capable of halting or reversing fibrosis progression – particularly in MASH – remain lacking. In recent years, incretin-based therapies, including glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and a new generation of metabolic multi-agonists, have gained breakthrough significance. These agents demonstrate potent metabolic, anti-inflammatory, and anti-steatotic effects, as well as potential antifibrotic activity, making them promising candidates for the treatment of various CLD phenotypes, including MASLD/MASH-associated fibrosis. This review synthesizes current knowledge on the mechanisms of action of these drugs, clinical trial outcomes, and their potential application as novel, targeted therapies in CLDs.